Analysis of Fine Art Learning to Stimulate Creativity in Kindergarten - Widya Dwi Hardiyanti; Prayitno Prayitno; Joko Pamungkas (Aulad: Journal on Early Childhood, 2025)
Creativity is an important skill in the 21st century. One of the activities to develop creativity is through the fine arts. This study aims to describe the process of fine art learning in early childhood to develop creativity. This research is a case study approach. The subjects consist of children and teachers at Aisyiyah XI and Nurul Hidayah Kindergarten Surakarta. Analysis data using the Miles, Huberman, and Saldana Models. The results of the study show that the art learning activities carried out include drawing and colouring, painting, mosaics, montage, and collaborative work using blocks and lego. Art learning methods can promote free expression, demonstration, and collaboration. The most effective method to stimulate a child's creativity is to allow the child to express their thoughts and feelings freely. The artworks of free expression-based learning are more varied because they align with the creativity of early childhood.